Pendampingan Pembuatan Media Pembelajaran Berbasis Teknologi Di SDN Tamberu 1 Pamekasan - Amalia, Laili; Anjarani, Devie Reztia; Lanya, Harfin; Hakim, Arif Rahman; Ismail Ismail (Fakultas Teknik Universitas Cenderawasih, 2023)
Learning media can stimulate students to remember what they have learned. Currently, technology sophistication delivers information and knowledge quickly. This has a big impact on educational progress. However, based on observations and interviews with the Principal of SDN Tamberu 1, information was obtained that most teachers were unable to use technology wisely even though the school had 6 laptop units, wifi to support the learning process. Technology is only limited on telephone, WhatsApp, or other applications such as TikTok. The partner problems is the lack of teacher competence and the use of technology-based learning media. The aim of this service is to provide solutions and assistance in creating technology-based media, especially at SDN Tamberu 1 Pamekasan. The targeted output are (1) An increasing in partners' knowledge about technology-based media (2) Implementation of technology media in learning (3) articles in accredited national journals and electronic media, (4) videos in electronic media